Densidade de aves e tipos de cama na criação de frangos de corte no ecótono Amazônia Cerrado: Desempenho e uso da termografia na identificação de pododermatite. - Costa, Hérica de Araujo (Universidade Federal do Tocantins, 2023)
Two experiments were conducted to evaluate the performance, meat quality the use of thermography to detect signs of pododermatitis of broiler chickens reared on two different litter materials and at two stocking densities. In experiments I and II, 216 one day-old Cobb 500® broiler chicks of mixed sex with a mean initial weight of 54 ± 3.37 g were used. The chicks were allotted in a completely randomized design (CRD) in a 2x2 factorial arrangement: two litter materials (wood shavings and rice hulls) and two stocking densities (24 and 30 kg/m2), totaling four treatments (rice hulls and 24 kg/m2, rice hulls and 30 kg/m2, wood shavings and 24 kg/m2 and wood shavings and 30 kg/m2) and six replicates. In experiment I, the following variables were evaluated: feed intake, weight gain, feed conversion, carcass yield and prime cuts, the blood parameters, total proteins and albumin, edible viscera, immune organs, intestine weight and length, abdominal fat, breast meat color, pH and shear force. In experiment II, the values of litter pH, moisture and temperature, the visual score and the maximum and minimum surface temperatures and thermal amplitude of the plantar surface of the footpad of broilers from 28 to 42 days of age were evaluated. In experiment I, the different litter materials did not influence feed intake, weight gain, and body weight but it affected the feed conversion. The different stocking densities influenced feed intake and weight gain, with no effect on feed conversion and body weight. There was an interaction between litter material and stocking density for feed intake, weight gain, feed conversion and body weight at 42 days of age. Litter materials and stocking densities did not affect the yields of carcass, drumstick, and thigh. However, there was an effect of stocking density on breast yield. The relative weight of the edible viscera, the immune organs, the weight and length of the small intestine, the meat quality and the blood parameters were not influenced by the treatments. However, the litter material influenced the abdominal fat and the enzyme aspartate aminotransferase (AST). In experiment II, there was no interaction between litter materials and different stocking densities for maximum and minimum temperatures and thermal amplitude. However, the minimum temperature and the thermal amplitude were influenced by different litter materials and stocking densities, with no effect on the maximum temperature. The stocking densities and litter materials did not influence the values of litter pH, moisture and temperature, and the visual score of the plantar surface of the footpad of broilers slaughtered at 42 days of age. It was concluded that the bed of shavings and the density of 24 kg / m² presented the best performance results for broiler chickens from one to 42 days of age and that the thermography was efficient to show that broiler chickens raised on bed of rice straw and density of 30 kg / m², presented lower minimum temperatures in the plantar cushion, indicating indications of lesions of pododermatitis from 28 to 42 days of age.